Compostos orgânicos voláteis de plantas e o etanol no controle de Meloidogyne incognita - Silva, Julio Carlos Pereira da (2016)
Volatile organic compounds (VOCs) emitted by plants may have activity against fitonemetoides. In this work, VOCs emitted by dry and aqueous macerates of broccoli inflorescence or sunflower seed were studied by their toxic effect to Meloidogyne incognita in different exposition times. VOCs emitted by sunflower seed and the broccoli inflorescence showed nematicidal activity on M. incognita second stage juveniles (J2) even in short periods of exposition. The infectivity and reproduction decreased when the J 2 were exposed to sunflower VOCs. Soil biofumigation with broccoli or sunflower macerates in different concentrations reduced the infectivity, reproduction and increased toxicity of VOCs emitted by plants. The water exposed to VOCs emitted by broccoli caused high immobility to the J2 in a few hours, but there was no toxic effect of water when exposed to sunflower seed macerate. Macerates GC-MS identified VOCs, in 6 and 5 chemical groups, by sunflower seeds and broccoli inflorescence, respectively. Furthermore, 8 molecules have been characterized on the exposed toxic water broccoli inflorescence. The volatile alcohol ethanol can be toxic to plant pathogens and it is not dangerous to humans. Aqueous dilutions of 5% ethanol to 70% and its vapors caused acute in vitro toxicity to M. icognita J2. The vapors and aqueous solutions of ethanol also caused low J2 hatching in nematode eggs. The higher reduction galls and egg on lettuce roots, happens when ethanol was applied to infested soil concentrations of 40% and 70% and at dosages of 40 ml and 80 ml. The water exposed to ethanol vapors for short periods of time acquired toxicity and caused 100% J2 mortality with 12 hours of exposition. The inflorescences of broccoli and sunflower seeds macerates showed toxic activity directly in soil and together with volatile emission, but the molecules emitted by broccoli inflorescences that were retained in the water need to be studied individually to better understanding of their effects. The ethanol effects on M. incognita in greenhouse open prospects for its use in the field controlling plant parasitic nematodes, especially in organic agriculture and broadleaf crops.